La comprensión de textos especializados. Un estudio polifónico-argumentativo sobre las dificultades de lectura en los estudios de formación docente en la Argentina - Tosi, Carolina (Universidad de Costa Rica, 2017)
A number of linguistic studies have argued that the reading comprehension issues presented by students in higher education respond to the lack of early development of literacy skills associated with study texts. Within this perspective, this paper shows that the main difficulties of academic reading presented by tertiary students are related to the inadequacy of the reading practice of specialized texts as well as to the lack of skills in metalinguistic reflection. To carry out the research, we worked with a population of incoming students to a teacher training program for Primary and Initial Education at the City of Buenos Aires (Argentina) and implemented a participant-observer research methodology. The process of data elaboration was predominantly qualitative and the corpus of analysis was made up of sixty-three written productions, corresponding to an activity of reading comprehension carried out on an argumentative text. The obtained results show that the main issues involving reading skills are linked with certain enunciative and polyphonic aspects of the texts. Throughout the analysis, the difficulties detected are systematized and are associated with the characteristics of the discursive configuration of textbooks, which constitute the main study material of secondary schools. Finally, the study demonstrates the importance of implementing “facilitating strategies” that foster students' metalinguistic reflection in order to improve their reading comprehension.